PENGARUH INOVASI TIM TERHADAP KINERJA TIM DENGAN BUDAYA TIM SEBAGAI VARIABEL MODERASI DI KOPINKRA SATYA BHAWANA KASONGAN, KABUPATEN BANTUL - Dody Rahmat Sholihin (NATAPRAJA, 2015)
ormance in ceramic potter teams and analyze the influence of team culture as a moderating variable in relation to team innovation on team performance in Cooperative Industrial Ceramics (Kopinkra) Satya Bhawana in Bantul, Yogyakarta. The used Testing in this study was linear regression and interaction test (MRA). The results of this study include, among others: first, team innovation have significant positive effect on team performance in Kopinkra Satya Bhawana. Effect of team innovation on team performance is 2,137 with a significant level of to 0,000. This condition is caused by some progressive craftsmen that produce objects which have the advantages of modern decorative material capital, symbolic and cultural. Second, the effect was not significant in the team culture moderate the relationship team innovation on team performance. Coefficient of moderation in influencing the performance of the team in Kopinkra Satya Bhawana is 0.001 with a significance level of 0.982. The reason is the process of coordinating the team as part of a team culture that carried the team in Kopinkra Satya Bhawana potter not in balance.Keywords: Team Innovation, Team Performance, Team Culture, Cooperative